Tropical paleoglacial geoheritage inventory for geotourism management of Chirripó National Park, Costa Rica - Quesada Román, Adolfo (2020)
Globally, most active tropical glacial landscapes are found at elevations above 4000 m. Nonetheless, the presence of paleoglacial landforms in low latitudes, especially those formed during the Last Glacial Maximum (LGM), persists in different tropical regions. Chirripó National Park, in central-south Costa Rica, is one of these particular examples. The glacial and periglacial landscape in the park are located over 3000 m, with landforms such as arêtes, glacial cirques, moraines, till deposits, and glacial lakes. We performed an integrated approach for the geoheritage inventory and geotourism management, crossing geomorphological and cultural information. A total of 14 geomorphosites were assessed and their management discussed. These geomorphosites achieved scientific scores between 0.5 (Valle Talari, Cerro Urán, and Cerro Terbi) and 0.88 (Cerro Chirripó and Los Crestones). The average scientific value of the geomorphosites is 0.75, since they are well preserved (0.75), rare (0.57) and representative (0.84) of the region’s geomorphology. They also play an important role in the geographical history (0.62), as well as the significant use and management characteristics (0.8). Chirripó National Park has key importance both naturally and culturally for Costa Rica. Its geomorphosites assessment is of critical value for the Costa Rican Conservation Areas System in order to promote improved geotourism. Geoheritage mapping can offer more opportunities of transferring geoscience knowledge to a larger public and policy makers. Our study aims to improve and further the state of the art of tropical glacial geoheritage.